Expanding the CRISPR/Cas toolkit: applications in proteomics and theranostics - Punde, Ashwini; Dey, Saurabh; Pandire, Riya; Bhattacharjee, Arindam; Patra, Chinmoy (Frontiers in Bioengineering and Biotechnology, 2025)
Conventional methods available for genome editing have proven non-specific, labour-intensive, and time-consuming. In this context, CRISPR/Cas technology represents a significant breakthrough. It is derived from a sophisticated microbial defence system consisting of clustered regularly interspaced short palindromic repeats, or CRISPR, and the RNA-guided DNA endonuclease Cas. Beyond its original role in genome editing, CRISPR continues to play a major role in the field of proteomics, functional genomics, and molecular therapy. Animal models, including mice, Drosophila, zebrafish, etc., have substantially benefited from CRISPR in uncovering protein function through reverse genetics approaches, including knock-in, knockout, CRISPRi, and indel mutation strategies. On the clinical front, CRISPR gene therapy has also seen successes, including applications in sickle cell disease, hypercholesterolemia, and cancer immunotherapy. However, notable challenges remain, including in vivo packaging and delivery efficiency, toxicity, and genomic off-target effects. Ongoing efforts to overcome these include the development of novel delivery formulations (e.g., nanoparticles, exosomes), artificial intelligence-guided experimental design, and miniaturization of Cas proteins. This review focuses on CRISPR/Cas gene editing mechanisms and explores its state-of-the-art applications in the field of proteomics and theranostics.